2014
DOI: 10.1051/0004-6361/201322404
|View full text |Cite
|
Sign up to set email alerts
|

The accretion environment in Vela X-1 during a flaring period usingXMM-Newton

Abstract: We present analysis of 100 ks contiguous XMM-Newton data of the prototypical wind accretor Vela X-1. The observation covered eclipse egress between orbital phases 0.134 and 0.265, during which a giant flare took place, enabling us to study the spectral properties both outside and during the flare. This giant flare with a peak luminosity of 3.92 +0.42 −0.09 × 10 37 erg s −1 allows estimates of the physical parameters of the accreted structure with a mass of ∼10 21 g. We have been able to model several contribut… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
88
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(93 citation statements)
references
References 31 publications
(51 reference statements)
4
88
1
Order By: Relevance
“…This is consistent with observations which showed that flares in Vela X-1 last from 10 2 s up to 10 4 s (see Ducci et al 2009;Martínez-Núñez et al 2014, and references therein).…”
Section: Double-peaked Sample Phase-resolved Spectroscopysupporting
confidence: 93%
See 2 more Smart Citations
“…This is consistent with observations which showed that flares in Vela X-1 last from 10 2 s up to 10 4 s (see Ducci et al 2009;Martínez-Núñez et al 2014, and references therein).…”
Section: Double-peaked Sample Phase-resolved Spectroscopysupporting
confidence: 93%
“…Inhomogeneous stellar winds from supergiant stars (so-called clumps) are expected (Runacres & Owocki 2005) and observed (Goldstein et al 2004, and references therein), and have been suggested as the cause for Vela X-1 flaring activity (see Kreykenbohm et al 2008 andMartínez-Núñez et al 2014). The timescale on which clumps hit the X-ray pulsar is on the order of the wind's dynamic timescale 0.5R B v ∞ ∼ 10 11 cm 1100 km s −1 ∼ 1000 s (2) where 0.5R B is the average separation between clumps (Sundqvist et al 2010).…”
Section: Double-peaked Sample Phase-resolved Spectroscopymentioning
confidence: 96%
See 1 more Smart Citation
“…These sources are usually considered to be prototypical for their respective classes (Martínez-Núñez et al 2014;Sidoli et al 2009;Mauche et al 2007). Hence, in addition to the important scientific value of studying these sources by themselves, this is an excellent opportunity to compare the donor parameters in these two prototypical systems, and to test how well the aforementioned resolutions for the SFXT puzzle fit with our results.…”
Section: Introductionmentioning
confidence: 99%
“…⋆ E-mail: sidoli@iasf-milano.inaf.it 1992, Sako et al 1999, Schulz et al 2002, Goldstein et al 2004, Watanabe et al 2006, Fürst et al 2010, Doroshenko et al 2013, Martínez-Núñez et al 2014 and references therein). These studies indicate the presence of both cold and hot gas components in the system, consistent with photoionization of the stellar wind produced by the X-ray pulsar, leading to the formation of a so-called photoionization wake trailing the neutron star (Fransson & Fabian 1980, Kaper et al 1994, Feldmeier et al 1996, van Loon et al 2001, confirmed by simulations (Blondin et al 1990, Blondin et al 1991, Mauche et al 2008).…”
Section: Introductionmentioning
confidence: 99%